2003
DOI: 10.1074/jbc.m302446200
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Inflammation and Edema Induced by Phospholipase A2

Abstract: Victims of snakebite quickly succumb to severe respiratory failure, which can be fatal if left untreated. One of the most toxic components of snake venom is phospholipase A 2 (PLA 2 ; EC 3.1.1.4). PLA 2 isolated from the elapid, Naja sputatrix, induced pulmonary inflammation and edema when administered intravenously and intratracheally to rats. Analysis of pulmonary gene expression profiles using oligonucleotide microarrays revealed 60 genes whose expression was altered by at least 3-fold in response to intrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The inflammatory events promoted by the venom may be attributed to hyaluronidase, PLA 2 , glycosylated proteins, SVSP and SVMP since they can promote different inflammatory events, which include complement activation, mast cell degranulation, release of eicosanoids and cytokines and leukocyte homing [16, 26, 27, 58, 59, 60, 61, 83]. Knowing that N .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflammatory events promoted by the venom may be attributed to hyaluronidase, PLA 2 , glycosylated proteins, SVSP and SVMP since they can promote different inflammatory events, which include complement activation, mast cell degranulation, release of eicosanoids and cytokines and leukocyte homing [16, 26, 27, 58, 59, 60, 61, 83]. Knowing that N .…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have noted the presence of different components in these venoms, including phospholipases A 2 (PLA 2 ), hyaluronidases (HYA) [13, 14, 15], metallo- (SVMP) and serine proteinases (SVSP) [16, 17, 18], inhibitors [19], peptides [20] and cytotoxins [21, 22]. All of these components may have cytotoxic [14, 23, 24], hemorrhagic, anticoagulant [25], pro-inflammatory [26, 27] or immunogenic [28] properties.…”
Section: Introductionmentioning
confidence: 99%
“…Cobra venom-derived secretory PLA2 (sPLA2) catalyzes the hydrolysis of membrane phospholipids to produce the lipid mediator, arachidonic acid (AA), which is further oxygenated into LTB4 by the enzyme 5-LOX (Ghassemi and Rosenberg, 1992; Rosenberg et al, 1983; Yates et al, 1990). PLA2 isolated from Naja sputatrix venom was reported to induce pulmonary inflammation and edema when administered intravenously and intra-tracheally to rats (Cher et al, 2003). Previous studies show that PLA2 plays a role in the worsening of cerebral ischemic injury in rodent models (Bonventre et al, 1997; Clemens et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Secretory PLA2 is the second biggest component of Naja sputatrix (Malayan spitting cobra) venom accounting for 15% of its dry weight only second to polypeptide cardiotoxins which comprise 60% of dry weight of the venom 18–20 . Previous study showed that sPLA2 isolated from Naja sputatrix venom induced pulmonary inflammation and edema when administered to rats 21 . Mice lacking PLA2 when subjected to cerebral ischemia had smaller infarcts, reduced brain edema and neurological deficits 22 .…”
Section: Introductionmentioning
confidence: 97%